2020
DOI: 10.1051/0004-6361/201937381
|View full text |Cite
|
Sign up to set email alerts
|

A new set of atmosphere and evolution models for cool T–Y brown dwarfs and giant exoplanets

Abstract: We present a new set of solar metallicity atmosphere and evolutionary models for very cool brown dwarfs and self-luminous giant exoplanets, which we term ATMO 2020. Atmosphere models are generated with our state-of-the-art 1D radiative-convective equilibrium code ATMO, and are used as surface boundary conditions to calculate the interior structure and evolution of 0.001 − 0.075 M objects. Our models include several key improvements to the input physics used in previous models available in the literature. Most … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
280
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(293 citation statements)
references
References 198 publications
(375 reference statements)
13
280
0
Order By: Relevance
“…Lacis & Oinas (1991); Pierrehumbert (2010)), and is extensively used for radiative transfer calculations in the context of planetary and substellar atmospheres (see, e.g. Irwin et al 2008;Showman et al 2009;Freedman et al 2008Freedman et al , 2014Lee et al 2019;Mollière et al 2015;Amundsen et al 2014;Sharp & Burrows 2007;Malik et al 2017;Drummond et al 2016;Phillips et al 2020). K-tables are generally considered faster (and more accurate for the same R = λ ∆λ ) than cross sections, but they also come with their own assumptions and therefore limitations (see, e.g.…”
Section: K-tablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacis & Oinas (1991); Pierrehumbert (2010)), and is extensively used for radiative transfer calculations in the context of planetary and substellar atmospheres (see, e.g. Irwin et al 2008;Showman et al 2009;Freedman et al 2008Freedman et al , 2014Lee et al 2019;Mollière et al 2015;Amundsen et al 2014;Sharp & Burrows 2007;Malik et al 2017;Drummond et al 2016;Phillips et al 2020). K-tables are generally considered faster (and more accurate for the same R = λ ∆λ ) than cross sections, but they also come with their own assumptions and therefore limitations (see, e.g.…”
Section: K-tablesmentioning
confidence: 99%
“…There are tools available online, such as the exo-k library 1 (Leconte et al, in prep), which enable conversion between different formats, some of which are those used in this work. Many other works have computed opacities for use in radiative-transfer retrieval and atmospheric modelling codes; see, for example, Showman et al (2009), Freedman et al (2008), Freedman et al (2014), Lee et al (2019), Amundsen et al (2014), Kempton et al (2017), Grimm & Heng (2015), Malik et al (2019), Kitzmann et al (2020), Allard et al (2012), Sharp & Burrows (2007), Line et al (2013), Gandhi & Madhusudhan (2017), Phillips et al (2020), Jørgensen (1998), Kurucz & Bell (1995).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, throughout this study we focus our efforts on the TW Hya Association (TWA) (Kastner et al 1997;Gagné et al 2018a) and the Pictoris Moving Group ( PMG) (Zuckerman et al 2001;Gagné et al 2018a). Both of these moving groups occupy a unique region of parameter space, with ages old enough that planetary formation processes have largely ended due to disk clearing (Haisch et al 2001), ages young enough that any potentially formed planets have retained a significant amount of heat from their initial gravitational contraction and are therefore more luminous (Baraffe et al 2003;Phillips et al 2020), and distances close enough to more favourably probe the innermost architectures of planetary systems through direct imaging. Although many other moving groups fulfil one or even two of these qualities (Gagné et al 2018a), currently TWA and PMG present the best opportunity to fulfil all three at once and are hence chosen for this investigation.…”
Section: Young Moving Group Selectionmentioning
confidence: 99%
“…Furthermore, recent work has suggested that the high nucleation energy barrier of Na 2 S strongly inhibits its formation and therefore its inclusion as a dominant cloud species may not be strictly accurate (Gao et al 2020). For these reasons, and as none of the ATMO models of Phillips et al (2020) include the effects of cloud opacity, we select the solar metallicity petitCODE models without any cloud opacity and retain model consistency between mass ranges.…”
Section: Mass Sensitivity Estimation: Model Selectionmentioning
confidence: 99%
See 1 more Smart Citation